PENGARUH PENUNDAAN WAKTU PERENDAMAN DAN PELUKAAN MEKANIS TERHADAP KUALITAS LADA PUTIH MUNTOK - Kamila Kamila; Riwan Kusmiadi; Siti Nurul Aini (Universitas Trilogi, 2019)
The quality of Muntok white pepper can be improved through a good immersion process, with regard to several activities such as immersion time delaying and thresing. This research was conducted at experimental farm of Bangka Belitung University and quality testing in UPTD, Certification and Quality Control, Laboratorium, Departement of Industry and Commerce Bangka Belitung islands. This study used factorial completely randomized design with two factors. The first factor (A) was consisted of 4 levels of immersion time delaying: (A0) without delaying, (A1) 2 days, (A2) 4 days and (A3) 8 days. The second factor (B) was threshing, consist: (B1) without threshing, (B2) threshing. The results showed that immersion time delaying could incerase the blackish seeds levels, foreign matter levels, and mold contamination levels. Two days and four days immersion time delaying were the optimum limit to maintain a better quality of pepper in term of blackish seed levels, foreign matter levels, volatile oil levels, piperine levels, water content and light seed content. The interaction effect of threshing and immersion time delaying hads no effect on the blackish seeds levels, foreign matter levels, mold contamination levels and essential oils levels. Keywords: white pepper, immersion, delaying, threshing